Complex Systems: Solutions and Challenges in Economics, Management and Engineering Dedicated to Professor Jaime Gil Aluja (Studies in Systems, Decision and Control,, 2018)
This book presents an authoritative collection of contributions reporting on fuzzy logic and decision theory, together with applications and case studies in economics and management science. Dedicated to Professor Jaume Gil Aluja in recognition of his pioneering work, the book reports on theories, methods and new challenges, thus offering not only a timely reference guide but also a source of new ideas and inspirations for graduate students and researchers alike.